2010
DOI: 10.1111/j.1365-2648.2010.05378.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of drug use and ageing: health, quality of life, relationship and service implications

Abstract: roe b., beynon c., pickering l. & duffy p. (2010)Experiences of drug use and ageing: health, quality of life, relationship and service implications. Journal of Advanced Nursing66(9), 1968–1979.AimThis paper is a report of an exploration of older people’s experiences of substance use in the context of ageing, and its impact on health, quality of life, relationships and service use.BackgroundUse of illicit drugs by older people is a neglected policy, research and service provision and is generally perceived as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
1
32
0
16
Order By: Relevance
“…Os velhos utilizadores de droga têm uma morbilidade superior a população em geral (Hser et al citados por Roe, et al, 2010) e sofrem mais de isolamento social, stress e medo de ser vitimizados (Levy & Anderson, 2005).…”
Section: O Envelhecimentounclassified
See 3 more Smart Citations
“…Os velhos utilizadores de droga têm uma morbilidade superior a população em geral (Hser et al citados por Roe, et al, 2010) e sofrem mais de isolamento social, stress e medo de ser vitimizados (Levy & Anderson, 2005).…”
Section: O Envelhecimentounclassified
“…Estudos (Roe, et al, 2010) demonstram problemas de saúde associados ao envelhecimento: circulatórios (tromboses venosas profundas, úlceras nos locais de punção), golpes, problemas respiratórios, diabetes, hepatite e cirrose, malnutrição, perda de peso, obesidade, mobilidade comprometida. Consequências na saúde mental, perda de memória, paranóia, mudanças de humor com ansiedade e fúria.…”
Section: O Envelhecimentounclassified
See 2 more Smart Citations
“…Results from literature and e-Labs indicated that mental health problems are common among the older OMT population (Dürsteler-MacFarland, Schmid, & Vogel, 2010;KOR-FOR, 2015;Roe, Beynon, Pickering, & Duffy, 2010;Rosen, Smith, & Reynolds, 2008). Individuals often suffer from memory loss, paranoia, changed mood or anger.…”
Section: Mental Healthmentioning
confidence: 99%